The STOP Program: a Hybrid Smoking Prevention and Cessation Training for Cancer Care Providers in Colombia and Peru - Tami-Maury, I (2023)
We designed and tested the feasibility of the Smoking Cessation Training Program for Oncology Practice (STOP), a hybrid (face-to-face plus web-based) educational intervention to enhance Spanish-speaking cancer care professionals’ (CCPs’) ability to provide brief smoking prevention and cessation counseling to cancer patients and survivors. Changes in the CCPs’ competencies (knowledge, attitude, self-efficacy, and practices toward smoking and smoking cessation services) were assessed post-training. Sixty CCPs from one major cancer center in Colombia (n = 30) and Peru (n = 30) were invited to participate in a 4-module hybrid training program on smoking prevention and cessation. Demographic and pre- and post-test evaluation data were collected. The training’s acceptability was measured after each module. Bivariate analysis was conducted using Wilcoxon signed-rank test to compare the CCPs’ competencies before and after the delivery of the STOP Program. Effect sizes were computed over time to assess the sustainability of the acquired competencies. Twenty-nine CCPs in Colombia and 24 CCPs in Peru completed the STOP Program (96.6% and 80.0% retention rates, respectively). In both countries, 98.2% of the CCPs reported that the overall structure and organization of the program provided an excellent learning experience. The pre-post-test evaluations indicated that the CCPs significantly improved their knowledge, attitude, self-efficacy, and practices toward smoking, smoking prevention, and cessation services. We found that the CCPs’ self-efficacy and practices increased over time (1-, 3-, and 6-month assessments after completing the 4 educational modules). The STOP Program was effective and well-received, demonstrating remarkable changes in CCPs’ competencies in providing smoking prevention and cessation services to cancer patients. © 2023, The Author(s).